INTERMEDIAL WRITING IN CONTEMPORARY THEATRE - Thenon , Luis (2013)
Contemporary narratives are part of a concept of designing as manipulation of space perception which is one of the decisive tools at a transforming, composed frame of resonances. It is possible to talk about a new artistic ecology, particularly at drama. Influenced by cinema and technology of image and sound, the renovation of contemporary drama thought is based on a multiplication of diegesis in superposition, fragmentation of narratives and relational praxis giving power to the contemporary intermedial scene.